Socialization of the Crime of Bullying in SMP 3 Bandar Lampung: Creating a Bullying-Free School - Rini Fathonah; Mashuril Anwar; Nikmah Rosidah; Erna Dewi; Hurriyah Ainaa Mardiyah; Andre Arya Pratama (Jurnal Pengabdian Masyarakat Bestari, 2023)
The specific purpose and target of this community service activity are to explain how criminal policies deal with bullying against children and provide legal assistance to victims of bullying. Community service activities use presentation, discussion, and question-and-answer methods. This activity was carried out on Monday, May 22, 2023, at 8:00 a.m. WIB until finished. Based on the results of the implementation of activities, the forms of bullying that occur at school are disturbing friends when studying, calling them by nicknames or titles, borrowing things without permission, calling parents' names, bullying friends by throwing paper in the form of toy airplanes, and physically, among others, hitting, holding shoulders and bodies, and stomping feet. Efforts to overcome bullying in schools are carried out through penal and non-penal efforts.